2011
DOI: 10.1007/s00345-011-0728-6
|View full text |Cite
|
Sign up to set email alerts
|

Is it suitable to eliminate bone scan for prostate cancer patients with PSA ≤ 20 ng/mL?

Abstract: PurposeWe evaluated the relationship between bone metastasis (BM) and clinical or pathological variables, including the serum prostate-specific antigen (PSA) concentration.MethodsThis retrospective study included 579 consecutive patients with newly diagnosed prostate cancer (Pca) who underwent a bone scan study at our institution between 2002 and 2010. We used receiver operating characteristics curves to evaluate accuracy of bone metastasis between serum PSA 10 and 20 ng/mL.Results A positive bone scan result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Similar findings were found in Pakistan, where there was an overall increased incidence of bone metastasis in newly diagnosed patients with prostate cancer and even at serum PSA level≤20 ng/ml and Gleason score <8 (Zaman et al, 2011). In Korea, 27 men (4.6%) with serum PSA between 10 and 20 ng/mL, 29/579 men (5.0%) with GS≤7, and 21/83 (25.3%) with serum PSA≤20 ng/mL and Gleason score (GS)≤7 had positive bone scans (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found in Pakistan, where there was an overall increased incidence of bone metastasis in newly diagnosed patients with prostate cancer and even at serum PSA level≤20 ng/ml and Gleason score <8 (Zaman et al, 2011). In Korea, 27 men (4.6%) with serum PSA between 10 and 20 ng/mL, 29/579 men (5.0%) with GS≤7, and 21/83 (25.3%) with serum PSA≤20 ng/mL and Gleason score (GS)≤7 had positive bone scans (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The false-positive rate was higher in our study (20%) than in previous studies, 12,13 perhaps due to the higher percentage of patients with bone metastasis in our study. However, other studies have reported even higher percentages of bone metastasis, including studies by Al-Ghazo and colleagues 15 (98 patients, 39.7% had bone metastasis), Lai and colleagues 16 (116 patients, 29.3% with metastasis), Kosuda and colleagues 17 (1294 patients, 22% with metastasis), and Lee and colleagues 11 (579 patients, 14.3% with metastasis). Therefore, the percentage of bone metastasis in our study was not unusually high.…”
Section: Discussionmentioning
confidence: 91%
“…16 Lai and colleagues 16 suggested that guidelines for Asians might differ from those for Caucasians. Lee and colleagues 11 showed the need for a bone scan in patients with PSA values of 10 to 20 ng/mL and suggested that new guidelines might be needed for Asians. In our study of Korean patients, 16 (2% of total patients) had bone metastases, even though none of the 4 guidelines recommended a bone scan for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the studies in which PSA and GS values are separately assessed to predict bone metastasis in PCa, there is also a number of studies in the literature in which both parameters are combined and the evaluation is made in this way, which is suggested to be more useful in predicting bone metastases (7,18,19).…”
Section: Discussionmentioning
confidence: 99%